Leader readiness of Gen Z in VUCA business environment. Issue 2 (9th September 2020) - Deepika,; Chitranshi, Jaya
Abstract : Purpose: The purpose of this paper is to focus on the leadership competencies of the Z generation (born after 1997) in the VUCA business environment. In today's scenario, the business works differently than it used to previously. The young workforce wants not just to contribute their energy to the organisation but to their colleagues and themselves too, with the leading global sceneries. Design/methodology/approach: An unstructured questionnaire was prepared by testing the reliability and validity of the data. Multiples linear regression analyses were used to derive results and to check whether the competencies are dependent on the VUCA skill sets. Entrepreneurial leadership, enabling leadership, operational leadership and architectural leadership are chosen to be the independent variables for this study. Findings: The findings reveal that the dependability is on all the four factors for the VUCA business environment and hence the need is to practice the same in the organisation. Research limitations/implications: The test has been done on a sample having 260 respondents. This study reveals data of the workspace environment only and not how Gen Z will behave to the conditions as individuals. Gender-perspective is not taken into account in this study. Practical implications: The implications can be seen for the organisations' understanding of how to deal with generation Z and empower them. The organisation-structure and processes that were developed previously will not be limited now just to making the organisations function but also impact self-development for Gen Z, the development that is focussed on work-teams of Gen Z and so the global market eventually. Originality/value: The originality is in the variables that have been taken for this study. As the world is growing rapidly, the mind-set and the style in which the manager works are changing. Therefore, it is necessary to take into account what leadership style will affect the current business environment.